Indonesian Demand for Online Shopping: Revisited - Syarifudin Yahya; Prof. Catur Sugiyanto, M.A. Ph.D (Journal of Indonesian Economy and Business (JIEB), 2020)
Introduction/Main Objectives: This study aims to analyze the factors that influence online shopping. Data are aggregated at the national, island, and regional levels. The regions are categorized based on their level of demand for online shopping. Background Problems: The rapid development of information and communications technology contributes to the transformation of the digital economy. By using 281,185 internet users from the National Households Survey (Survei Sosial Ekonomi-Susenas) 2017 data, we found that the percentage of online shopping in Indonesia is 7.59%. Online shopping is concentrated on the island of Java, especially in the Greater Jakarta area (Jakarta, Bogor, Depok, Tangerang, and Bekasi). Novelty: This study analyzes online shopping from the point of view of economic development studies, especially related to the development of information technology and the digital economy. Research Methods: We used a binary logistic regression analysis to assess the effect of demographic, socio-economic, and spatial factors on an individual’s decision to shop online. Finding/Results: The results indicate that individuals who have a greater tendency to shop online are those who have a high income, are women, can access the internet using mobile phones, they are the spouses of the heads of households, are 25 to30 years old, live in urban areas, have graduated from college (especially with a diploma), and work in the tertiary sector. The higher that the share of online shopping is in an area, the more intense the influence of individual characteristics will be on the tendency to shop online, according to the demographic and socio-economic factors, while the spatial factors will fade away. Conclusion: Income, gender, internet access, and the shopper’s position in the household are factors that significantly influence individuals to shop online.